2014
DOI: 10.7306/gq.1197
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of soil permeability from consolidation analysis based on Terzaghi’s and Biot’s theory

Abstract: 1 Uni ver sity of War saw, Fac ulty of Ge ol ogy, ¯wirki i Wigury 93, 02-089 Warszawa, Po land 2 Cra cow Uni ver sity of Tech nol ogy, Fac ulty of En vi ron men tal En gi neer ing, Warszawska 24, 30-155 Kraków, Po land Dobak, P., Gaszyñski, J., 2015. Eval u a tion of soil per me abil ity from con sol i da tion anal y sis based on Terzaghi's and Biot's theories. Geo log i cal Quar terly, 59 (2): 373-381, doi: 10.7306/gq.1197Proper eval u a tion of per me abil ity pa ram e ters has a cru cial sig ni fi ca tion i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…Given that this is a mono-objective problem, c v with the lowest error was selected and was considered as the optimal value for experimental results. Such approaches have been adopted and validated for various natural and artificial geomaterials by Dobak and Gaszyński [14], Olek and Pilecka [47] and Olek [45]. To carry out the GR method at a suitable level of accuracy, a function that could evaluate the error between the experimental and theoretical solutions and then minimise this function should be defined.…”
Section: Optimisation Msl Consolidation Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that this is a mono-objective problem, c v with the lowest error was selected and was considered as the optimal value for experimental results. Such approaches have been adopted and validated for various natural and artificial geomaterials by Dobak and Gaszyński [14], Olek and Pilecka [47] and Olek [45]. To carry out the GR method at a suitable level of accuracy, a function that could evaluate the error between the experimental and theoretical solutions and then minimise this function should be defined.…”
Section: Optimisation Msl Consolidation Testsmentioning
confidence: 99%
“…In other respects, research on laboratory measured pore water pressure highlighted that the derived vertical coefficient of consolidation, c v , differs significantly compared to that determined from compression data [14,44,48,49,53,66]. Robinson [51] proposed a linear relationship between pore water pressure and compression for determining c v .…”
Section: Introductionmentioning
confidence: 99%
“…Dumais and Komrad used the nonlinear relationships of effective stress, void ratio, and hydraulic conductivity to characterize the properties of thawing soil and established a onedimensional model for consolidation of thawing soil based on the large strain consolidation theory and heat-transfer equations [19]. Based on Terzaghi's theory, Dobak and Gaszyński obtained a parameter evaluation method related to compressibility and permeability coefficient and improved the one-dimensional consolidation test method [20]. Yazdani et al derived a set of nonlinear partial differential equations by utilizing the relationship between the void ratio and effective stress as well as the relationship between the void ratio and permeability, which are used to predict the consolidation characteristics of normally consolidated and overconsolidated soft clay subjected to cyclic loading [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Concerned about the state of such research at home and abroad, we identified three problems with previous study efforts (Ai et al, 2015;Bonomo et al, 2015;Dassanayake et al, 2015;Dobak et al, 2015;Rohan et al, 2020):…”
Section: Introductionmentioning
confidence: 99%